An interface crack with mixed electrical conditions at it faces in 1D quasicrystal with piezoelectric effect. Issue 23 (11th August 2022) - Loboda, V.; Sheveleva, A.; Komarov, O.; Lapusta, Y.
Abstract: An interface crack in 1D piezoelectric quasicrystalline space is considered. Both conducting and mixed conducting-permeable electric conditions at the crack faces are studied. The matrix–vector representations of the phonon, phason and electric quantities via the sectional-holomorphic function are derived. Two types of electrical conditions at the crack faces are considered – conducting case and mixed conducting-permeable case. A Riemann problem of linear relationship and a combined Dirichlet–Riemann boundary value problem are derived. Exact analytical solutions of the mentioned problems are presented and the simple analytical formulas for all required values are given and numerically illustrated.